Association of tenofovir disoproxil fumarate with primary allograft survival in HIV‐positive kidney transplant recipients. Issue 4 (28th July 2017) - Boyle, Suzanne M.; Malat, Gregory; Harhay, Meera N.; Lee, Dong H.; Pang, Lisa; Talluri, Sindhura; Sharma, Akshay; Bias, Tiffany E.; Ranganna, Karthik; Doyle, Alden M.
Abstract: Background: Tenofovir disoproxil fumarate (TDF) is an antiretroviral agent frequently used to treat human immunodeficiency virus (HIV). There are concerns regarding its potential to cause acute kidney injury, chronic kidney disease, and proximal tubulopathy. Although TDF can effectively suppress HIV after kidney transplantation, it is unknown whether use of TDF‐based antiretroviral therapy (ART) after kidney transplantation adversely affects allograft survival. Methods: We examined 104 HIV+ kidney transplant (KT) recipients at our center between 2001 and 2014. We generated a propensity score for TDF treatment using recipient and donor characteristics. We then fit Cox proportional hazards models to investigate the association between TDF treatment and 3‐year, death‐censored primary allograft failure, adjusting for the propensity score and delayed graft function (DGF). Results: Of the 104 HIV+ KT candidates who underwent transplantation during the study period, 23 (22%) were maintained on TDF‐based ART at the time of transplantation, and 81 (78%) were on non‐TDF‐based ART. Median age of the cohort was 48 years; 87% were male; 88% were black; and median CD4 count at transplantation was 450 cells/mm 3 . Median kidney donor risk index was 1.2. At 3 years post transplantation, primary allograft failure occurred in 26% of patients on TDF‐based ART and in 28% of patients on non‐TDF‐based ART ( P =.5). TDF treatment was not associated with primary allograft failure at 3 years post transplant after adjusting for DGF and a propensity score for TDF use (hazard ratio 2.12, 95% confidence interval 0.41‐10.9). Conclusions: In a large single‐center experience of HIV+ kidney transplantation, TDF use following kidney transplantation was not significantly associated with primary allograft failure. These results may help inform management for HIV+ KT recipients in need of TDF therapy for adequate viral suppression.